Association between anthropometry and upper-body strength qualities with sprint paddling performance in competitive wave surfers - Sheppard, J. M.; McNamara, P.; Osborne, M.; Andrews, M.; Oliveira, B. T.; Walshe, P.; Chapman, D. W. (The Journal of Strength and Conditioning Research, 2012)
This study aimed to evaluate the potential association with anthropometry and upper-body pulling strength with sprint kinematics of competitive surfers. Ten competitive male surfers (23.9 ± 6.8 years, 177.0 ± 6.5 cm, 72.2 ± 2.4 kg) were assessed for stature, mass, arm span, E 7 site skinfold thickness, pronated pull-up strength, and sprint paddling performance from a stationary start to 15 m. Pearson correlation analysis, and independent t-tests were used to compare potential differences between the slower and faster group of sprint paddlers. Strong associations were found between relative (total kilograms lifted per athlete mass) upper-body pulling strength and sprint paddling time to 5, 10, and 15 m, and peak sprint paddling velocity (r = 0.94, 0.93, 0.88, 0.66, respectively, p < 0.05) and relative upper-body pulling strength was found to be superior (p < 0.05) in the faster group, with large effect (d = 1.88). The results of this study demonstrate a strong association between relative upper-body pulling strength and sprint paddling ability in surfers. Strength and conditioning coaches working with competitive surfers should implement strength training with surfers, including an emphasis on developing relative strength, because this may have a strong influence on sprint paddling performance.